2017
DOI: 10.1007/s12272-017-0923-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic induction of apoptosis by combination treatment with mesupron and auranofin in human breast cancer cells

Abstract: Urokinase-type plasminogen activator (uPA) has been validated as a predictive or prognostic biomarker protein, and mesupron is considered the first-in-class anticancer agent to inhibit uPA activity in human breast cancer. In the present study, we showed that the synergism between mesupron and auranofin, a thioredoxin reductase inhibitor, for inducing of apoptosis in MCF-7 human breast cancer cells. Our results demonstrated that mesupron and auranofin significantly lead to inhibition of the cancer cells prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The sensitivity of gastric cancer cells to auranofin could be increased by the silencing of genes involved in autophagy [ 38 ], and BRCA1 deficiency has further been implicated to increase sensitivity of ovarian cancer cells to auranofin [ 39 ]. Synergistic activity on cancer cell growth in preclinical models is reported for the combination of auranofin with many anticancer agents and is in line with the use of auranofin as combination therapy in current clinical trials [ 24 , 25 , 36 , 40 , 41 ]. The sensitizing activity of auranofin is further supported by studies showing an enhancement of radiation response in breast cancer cells [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 53%
“…The sensitivity of gastric cancer cells to auranofin could be increased by the silencing of genes involved in autophagy [ 38 ], and BRCA1 deficiency has further been implicated to increase sensitivity of ovarian cancer cells to auranofin [ 39 ]. Synergistic activity on cancer cell growth in preclinical models is reported for the combination of auranofin with many anticancer agents and is in line with the use of auranofin as combination therapy in current clinical trials [ 24 , 25 , 36 , 40 , 41 ]. The sensitizing activity of auranofin is further supported by studies showing an enhancement of radiation response in breast cancer cells [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 53%
“…It is therefore listed by the World Health Organization as a member of the anti-rheumatic agent category. Lee found that synergy between mesupron and auranofin can be used to induce apoptosis in MCF-7 human breast cancer cells [48]. The results demonstrated that mesupron and auranofin significantly lead to inhibition of cancer cell proliferation; cell cycle arrest at the G1/S phase of the cell cycle; and apoptosis as indicated by caspase 3 activation, poly(ADP-ribose) polymerase cleavage, and annexin V staining.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, evaluating synergistic effects between repurposed classes of drugs may prove useful in circumventing resistant phenotypes through complementary blockade of discrete signaling pathways [ 71 , 72 ]. Whereas auranofin as a single-agent has shown limited usefulness, multiple independent studies are investigating its benefit as a cooperative agent [ 28 , 38 42 , 73 ]. It is possible that the value of auranofin lies in contributing specific insults alongside other classes of chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Auranofin has also been shown to be more effective in BRCA1-defective ovarian cells due to accumulations in unrepaired DNA damage [ 37 ]; however, this observation has not been confirmed clinically. Importantly, substantial evidence has demonstrated the synergistic enhancement of auranofin effects when used in combination with other compounds [ 28 , 38 42 ].…”
Section: Introductionmentioning
confidence: 99%